On Psychological Function of Metonymy in the Language of Fiction - A L Novikov; M A Rybakov (Peoples' Friendship University of Russia (RUDN University), 2013)
The article discusses the metonymy as a special technique of creative thinking. The authors suggest accentuating the psychological functions of the metonymy in addition to the lexical-semantic and stylistic functions on the basis of the analysis of the language of the twentieth century literature.